Exploring the impact of green roofs on chile pepper (Capsicum annuum l.) production, growth, and consumer acceptance - Gross, Eliza, author; Bousselot, Jennifer, advisor; Chavez, Maria, advisor; Ham, Jay, committee member; Bartolo, Michael, committee member; Calvert, Martha, committee member (Colorado State University. Libraries, 2025)
The progression of climate change is creating challenges for current agriculture systems with more intense and variable weather patterns as well as the degradation of land. In some places arable land has been converted for renewable energy production because of climate change challenges, but this further strains current food systems. Amidst this, the demand for food globally is also expected to increase while rapid urbanization takes place, which results in increased rates of food insecurity in urban areas. One solution may be rooftop agrivoltaics (RAV) which is a novel system that combines crop production on green roofs with photovoltaic (PV) arrays. This study explored the impact of RAV on chile pepper production and plant growth over two growing seasons to characterize this novel growing environment and better understand chile pepper suitability for such system. Season 2023 included four cultivars of chile peppers ('Mosco', 'Hatch', 'CSU', and 'Primrose') grown on the Hydro green roof located at the CSU Spur campus in Denver, Colorado. Each cultivar was grown in a full sun plot (control), in a plot under a bifacial PV array (treatment), and in a plot under an opaque PV array (treatment). Season 2024 focused on the first three cultivars with the addition of two treatment plots: 40% shade cloth treatment to simulate semi-transparent PV and an at grade plot for more direct comparison to traditional growing methods. Results demonstrated significantly decreased yield under bifacial and opaque PV arrays compared to full sun and shade cloth plots. Plant growth and biomass were significantly impacted by shade from the PV though results were not consistent across seasons. Stomatal conductance was reduced significantly in the first part of the growing season in the shade cloth, bifacial, and opaque plots suggesting reduced plant water use. Overall, the results demonstrated that the 40% shade cloth plot resulted in high yields and optimum plant growth. The use of semi-transparent panels could provide an ideal growing environment for effective chile pepper production in RAV while also producing renewable energy. Roasted chile peppers are a culturally important part of the diet to many Coloradoans, however little research has been conducted to understand how different growing environments may impact sensory attributes. 'Mosco' and 'Hatch' chile peppers grown in full sun on a green roof and at grade were roasted for sensory evaluation by consumers in Denver, Colorado. Samples were evaluated using a just-about-right (JAR) scale for 7 attributes and a standard 9- point hedonic scale for overall liking. There was no significant difference between treatments for each cultivar in overall liking. Panelists did show a slight preference for green roof grown roasted chile peppers compared to at-grade roasted chile peppers for each cultivar, and a desire for some attributes to be more intense was noticed in JAR results. Overall, urban farmers can confidently grow 'Mosco' and 'Hatch' chile peppers on green roofs without significant impact to consumer acceptance. Chile peppers are a suitable crop for growing both on green roofs and in certain RAV systems with additional considerations.
Keywords: green roof; rooftop agrivoltaics; chile peppers; urban agriculture; roasted chile peppers